(untitled) (Asian Journal of Medical and Biological Research, 2015)
The present study was undertaken to investigate the microbiological quality of poultry meat used in different hall of Bangladesh Agricultural University campus. Sanitary condition of dining hall was assessed by using a standard questionnaire. Thirty samples were collected from Isha Khan hall, Fazlul Haque hall and Taposhi Rabeya hall. Microbial load was determined by total viable count (TVC), total coliform count (TCC) and total salmonella count (TSC). Samples were inoculated into various selective media such as plate count (PCA) agar, xylose lysine deoxycholate Agar (XLDA) and MacConkey agar (MCA). It is found that the age of maximum workers (53%) is between 25-35 years. Educational level of dining workers are in same frequency of illiterate and below class eight. Only 6.7% are SSC passed. Most of dining workers have no knowledge on hygienic practices. 43.3% partially know about hygienic practices and 3.3% have no knowledge. Sanitary condition of dining hall is not satisfactory. Only 3.3% disinfectants are used in dining hall. There is no proper washing facilities. About 63.3% washing facilities are in medium level. Only E. coli and Salmonella spp. were isolated and identified from the samples. The mean value of TVC, TCC and TSC in broiler thigh meats of Isha Khan hall, Fazlul Haque hall and Taposhi Rabeya hall are log 5.65, log 5.77, log 6.06 CFU/g, log 3.26, 3.41, 3.42 CFU/g and log 2.95, log 2.92 log 2.97 CFU/g respectively. The variation of TVC in meats of different dining hall was significant (p<0.05) at 5% level of probability whereas TCC and TSC obtained from meat samples of different hall were not significant (p<0.05). Presence of Escherichia coli and Salmonella spp. in meat must need particular attention as these organisms are responsible for causing harm to public health. Suggestions have been given to improve the present sanitary condition of dining hall to minimize bacterial load. Asian J. Med. Biol. Res. June 2015, 1(1): 9-16